Aktivitas Fisik dan Kebiasaan Sedenter Memengaruhi Kesehatan Mental pada Anak di Masa Pandemi COVID-19 - Salsa Bellanisa Salsa Bellanisa; Lisa Adhia Garina; Umar Islami (UNISBA Press, 2023)
Abstract. The World Health Organization (WHO) declared Corona Virus Disease-19 (COVID-19) as a pandemic in March 2020. Until now, COVID-19 is still a global health problem that receives special attention in the world. The impact of the COVID-19 pandemic includes violence against community activities such as closing face-to-face schools, thus making children undergoing social isolation due to COVID-19 violence. Social isolation results in a decrease in physical activity and an increase in sedentary behavior so that it risks a bad psychological impact on children. The purpose of this study was to analyze the relationship between physical activity and sedentary habits with children's mental health during the COVID-19 pandemic. This study applies a scoping review study to analyze a scientific paper published in several journals. Of the 752 articles found in the three data sources, there were 7 articles that fulfilled the criteria for this study. The results in one of the articles indicated there is an increase in daily screen usage during quarantine (p<0.001). Other studies have shown that a lack of physical activity is associated with feelings of sadness in adolescents (p=0.01) and that increased use of social media is associated with higher levels of anxiety in adolescents (p=0.0077). Changes in physical activity and sedentary habits are closely related to the activation of stress hormones in the body, and if this continues for a long time, it can have an impact on the level of neurons in the hippocampus, causing symptoms of anxiety and even mental disorders in children. The conclusion of this study is that there is a relationship between physical activity and sedentary behavior with children's mental health during the COVID-19 pandemic. Abstrak. World Health Organization (WHO) menetapkan Corona Virus Disease-19 (COVID-19) sebagai pandemi pada Maret 2020. Sampai saat ini, COVID-19 masih menjadi salah satu masalah kesehatan global yang mendapat perhatian khusus di dunia. Dampak dari pandemi COVID-19 diantaranya yaitu pembatasan kegiatan masyarakat seperti penutupan sekolah tatap muka, sehingga membuat anak-anak menghadapi isolasi sosial akibat pembatasan COVID-19. Isolasi sosial mengakibatkan penurunan aktifitas fisik dan peningkatan perilaku sedenter sehingga berisiko dampak psikologis yang buruk pada anak. Tujuan penelitian ini adalah untuk menganalisis hubungan antara aktivitas fisik dan kebiasaan sedenter dengan kesehatan mental anak di masa pandemi COVID-19. Penelitian ini menerapkan studi scoping review untuk menganalisis suatu tulisan ilmiah yang dipublikasikan di beberapa jurnal. Dari 752 artikel yang ditemukan pada tiga sumber data, terdapat 7 artikel yang telah memenuhi kriteria penelitian ini. Hasil pada salah satu artikel menyebutkan adanya penggunaan layar harian yang meningkat selama karantina (p<0,001). Penelitian lainnya menunjukkan kurangnya aktivitas fisik berhubungan dengan perasaan sedih pada remaja (p=0,01) dan penggunaan media sosial yang meningkat berhubungan dengan tingkat kecemasan yang lebih tinggi pada remaja (p=0,0077). Perubahan aktivitas fisik dan kebiasaan sedenter berkaitan erat dengan aktifnya hormon stress dalam tubuh, dan jika terjadi berkepanjangan dapat berdampak pada tingkat neuron di hipokampus sehingga timbulnya gejala kecemasan bahkan gangguan mental pada anak. Simpulan dari penelitian ini didapatkan adanya hubungan aktivitas fisik dan perilaku sedenter dengan kesehatan mental anak di masa pandemi COVID-19.